Implementation of Information Communication Technology in Enhancing Early Childhood Language Development: - Sabarno Dwirianto; Trimasnia ziliwu, Tris (Yayasan Rahmatan Fidunya Wal Akhirah, 2023)
This study aims to determine the effect of using Information Communication and Technology in improving language development in early childhood. The research method used is true experimental research. The subjects of this study were children aged 4-6 years in grades B1 and B2, the number of group B1 was 17 children and the number of group B2 was 17 children. The data collection tool used is in the form of observation sheets for the language development of children aged 4-6 years after being treated with ICT-based learning media. The results of the t-test show that the asymp. Significant (2-tailed) of 0.012 with a significant value <0.06. The hypothesis is accepted, meaning that ICT-based learning media can improve the language development of children aged 4-6 years for the better. Therefore, researchers provide suggestions that educators can use internet media, computers and technology as an alternative in learning activities, especially in early childhood language development.